2017
DOI: 10.1037/pac0000264
|View full text |Cite
|
Sign up to set email alerts
|

Backfire of good intentions: Unexpected long-term contact intervention effects in an intractable conflict area.

Abstract: We investigated whether an intergroup contact intervention that included two intergroup meetings between Jewish and Arab Israeli students in Israel led to improved long-term intergroup relations. Besides our interest in long-term intergroup contact effects in an intractable conflict, we analyzed minority-majority differences in this context. Before we calculated our results, measurement equivalence across time was ascertained. Data were computed using latent change models. Results for minority members (Arab Is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Studies of both neighbourhoods (Koopmans and Veit 2014; Laurence, Schmid, and Hewstone 2017) and schools (ten Berge, Lancee, and Jaspers 2017;Bayram Özdemir et al 2018) show that as opportunities for positive-mixing increase so too do opportunities for negative mixing (Pettigrew 2008). Accordingly, youth engagement could also generate more negative contact experiences, which not only impede any positive impact of participation on youth attitudes but potentially generate worse outcomes than if young people had not participated at all (Conner and Erickson 2017;Guffler and Wagner 2017).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of both neighbourhoods (Koopmans and Veit 2014; Laurence, Schmid, and Hewstone 2017) and schools (ten Berge, Lancee, and Jaspers 2017;Bayram Özdemir et al 2018) show that as opportunities for positive-mixing increase so too do opportunities for negative mixing (Pettigrew 2008). Accordingly, youth engagement could also generate more negative contact experiences, which not only impede any positive impact of participation on youth attitudes but potentially generate worse outcomes than if young people had not participated at all (Conner and Erickson 2017;Guffler and Wagner 2017).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The type of contact participants experience appears crucial for understanding such differences in how participation affects intergroup attitudes (Erickson and O'Connor 2000;Conner and Erickson 2017;Guffler and Wagner 2017). In a study of Arab/Jewish youth in Israel, Guffler and Wagner (2017) found that involvement in an engagement programme had a short-term positive-effect on Arab youth. However, Jewish youth reported worsening attitudes post-participation, driven by reports of negative contact during engagement.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Negative contact is likely to be particularly relevant in applied contexts outside the laboratory where it is especially hard to achieve optimal contact conditions (Dixon et al, 2005). For exam-ple, Guffler and Wagner (2017) studied Jewish Israeli and Arab Israeli students in an intergroup contact intervention. Contrary to the authors' expectations, Jewish Israeli students reported worse attitudes towards Arab Israeli students following this contact intervention.…”
mentioning
confidence: 99%
“…Research teaches us that directly and assertively confronting the more dominant group with discrimination and injustice toward disadvantaged groups might indeed elicit empathy and moral concern (Shani & Boehnke, 2017). However, and at the same time, and just as often, such a confrontation can cause a defensive response of backlash (Guffler & Wagner, 2017;Ron, et al, 2020), further polarization and a more extreme justification of the existing status quo (Maoz, Bar-On, & Yikya, 2007;Mor et al, 2016). It is therefore crucial to carefully consider the specific circumstances, the readiness of the participants in the conversation, and the nature of the intergroup relations when using confrontation to evoke moral concern.…”
Section: Confrontation: When and Howmentioning
confidence: 99%